Externalities and House Prices: A Stated Preferences Approach - Michał Głuszak (Entrepreneurial Business and Economics Review, 2018)
Objective: In the article, we address the nexus between neighbourhood externalities and house prices using stated preference data. The impact of neighbourhood amenities generating positive externalities and disamenities generating negative externalities on property prices has been studied since the 1970s. Most of the studies to date applied the hedonic methodology and assumed that the effect is homogeneous. The article aims to address the potential heterogeneity of housebuyers’ preferences.